Risk assessment for digital transformation projects in construction Enterprises: an enhanced FMEA model - Li, Tangzhenhao; You, Jianxin; Aktas, Emel; Dong, Yongxin; Yang, Miying (Elsevier, 2025)
The digital transformation of the construction industry is crucial for advancing global digital economies, but it involves significant risks that require a standardized and robust assessment methodology. This paper presents an enhanced Failure Mode and Effect Analysis (FMEA) model that integrates the Multiple Attribute Border Approximation Area Comparison (MABAC) method with Grey Relational Analysis (GRA). Unlike previous approaches, this integration aligns grey relational changes with border approximation vector components, capturing both positive and negative correlations between modes. This enhances the prioritization process by distinguishing failure modes that may amplify or mitigate each other’s impact, leading to more precise risk assessments and mitigation strategies. The model also employs interval numbers instead of crisp numbers to reduce information loss from decision-making ambiguities caused by heterogeneous expert evaluations. Applied in a real-life case study, the improved model effectively accommodates biases and hesitations in expert decision-making, enhancing the accuracy and reliability of risk assessments in digital transformation projects. The findings highlight the model’s potential as a comprehensive and reliable framework for identifying, prioritizing, and mitigating risks in the digital transformation of the construction industry.
Keywords: 4005 Civil Engineering; 40 Engineering; 33 Built Environment and Design; 3302 Building; 2.2 Factors relating to the physical environment; Generic health relevance; Artificial Intelligence & Image Processing